An universal law of periodicity of catastrophes is in the nonlinear dynamic systems. Part 2. Non-linearity of the systems is investigation of their heterogeneity - Кузьменко, А.Г. (Problems of Tribology, 2014)
An universal law of periodicity of catastrophes is in the nonlinear dynamic systems. Part 2. Non-linearity of the systems is investigation of their heterogeneity